(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
Safeguarding minors and the vulnerable in the Church: a systemic approach "listening to reality" ABSTRACT: The dialogue and the "virtuous contamination" between canon law and extra-juridical disciplines, mainly of a socio-humanistic nature, are the main novelty in the management of the phenomenon of sexual abuse by the clergy against minors and vulnerable people, both from a practical point of view as well as from a juridical-normative one. With this aim, the paper deals with some "lessons" drawn from the experience gained in the painful circumstances of the abuses of the clergy, analyzing the contribution and the impact of some extra- juridical disciplines on a model of canon law that is not self-referential but open and transdisciplinary. SOMMARIO: 1. - La Chiesa “oltre” il diritto canonico: dialogo transdisciplinare e specificità ecclesiali - 2. Protezione vs salvaguardia: Child protection vs safeguarding - 3. Le lezioni dalla realtà e la loro “integrazione” nel diritto canonico - 3.1. L’ascolto delle vittime - 3.2. Non c’è prevenzione senza formazione - 3.3. Non c’è prevenzione senza cura - 3.4. Progettare le sanzioni e immaginare la riparazione - 4. Conclusioni. Salvaguardia dei minori e transdisciplinarietà del diritto canonico come cifra di una “Chiesa in uscita”. Luci e ombre di un percorso appena iniziato.